USE OF COCONUT HUSKS TO FACILITATE THE REMOVAL OF H2S FROM BIOGAS - Minza I. SELELE; Shaaban M. MGANA (Journal of Applied Life Sciences and Environment)
The study investigates the potential of coconut husks in purifying biogas, a common issue in the use of biogas due to the high costs and environmental impact of expensive purification technologies. The study used an experimental setup generating biogas from kitchen waste and analysed its composition using an industry-standard biogas analyser. Coconut husks could remove hydrogen sulphide (H2S), with a high percentage removal efficiency of 54% at a column length of 0.5 m from the inlet. Based on the results, 2 kg of coconut husk could purify 837 L of biogas, with a removal efficiency of approximately 62%, before exhaustion. This suggests that coconut husks can be used in biogas purification to remove H2S, which is the most challenging component as it can corrode metal parts when used at high concentrations above 750 ppm. Further research is needed on large-scale purification using coconut husks at high pressure to allow more gas adsorption by the purification media.